2017
DOI: 10.1016/j.stemcr.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem Cell-Derived Macrophages Share Ontogeny with MYB-Independent Tissue-Resident Macrophages

Abstract: SummaryTissue-resident macrophages, such as microglia, Kupffer cells, and Langerhans cells, derive from Myb-independent yolk sac (YS) progenitors generated before the emergence of hematopoietic stem cells (HSCs). Myb-independent YS-derived resident macrophages self-renew locally, independently of circulating monocytes and HSCs. In contrast, adult blood monocytes, as well as infiltrating, gut, and dermal macrophages, derive from Myb-dependent HSCs. These findings are derived from the mouse, using gene knockouts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
211
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(224 citation statements)
references
References 48 publications
(57 reference statements)
11
211
2
Order By: Relevance
“…16 Vanhee et al used a reporter hESC line with MYB-eGFP , a marker for hematopoietic stem cell (HSC)-dependent hematopoiesis, and confirmed the absence of in vitro generation of MYB + HSC during EB-based IPSDM differentiation. 16 The results were further validated in human iPSCs, 17 showing that knockout of MYB in iPSC by CRISPR/Cas9 did not impact IPSDM differentiation. 12 In contrast, when SPI1 and RUNX1 , important transcription factors in yolk sac (YS) hematopoiesis, were knocked out, iPSCs were unable to produce CD14 + macrophages.…”
Section: Generation Functional Feature and Molecular Profiling Of Ipsdmmentioning
confidence: 91%
“…16 Vanhee et al used a reporter hESC line with MYB-eGFP , a marker for hematopoietic stem cell (HSC)-dependent hematopoiesis, and confirmed the absence of in vitro generation of MYB + HSC during EB-based IPSDM differentiation. 16 The results were further validated in human iPSCs, 17 showing that knockout of MYB in iPSC by CRISPR/Cas9 did not impact IPSDM differentiation. 12 In contrast, when SPI1 and RUNX1 , important transcription factors in yolk sac (YS) hematopoiesis, were knocked out, iPSCs were unable to produce CD14 + macrophages.…”
Section: Generation Functional Feature and Molecular Profiling Of Ipsdmmentioning
confidence: 91%
“…To recapitulate the development of yolk sac-derived macrophages, we use our previously established, straightforward, highly efficient, serum- and feeder-free protocol for deriving PSC macrophages (Karlsson et al., 2008, van Wilgenburg et al., 2013). We have recently directly demonstrated that these derive from MYB -independent, RUNX1- and PU.1 -dependent precursors, characteristic of yolk sac-derived macrophages (Buchrieser et al., 2017, Vanhee et al., 2015). Here, we co-culture them with iPSC cortical neurons (Shi et al., 2012), in medium optimized for survival and functionality of both neurons and microglia.…”
Section: Introductionmentioning
confidence: 99%
“…Although our initial studies used HSPCs derived from murine bone marrow or human cord blood, also iPSC-derived macrophages represent a highly interesting source for cell therapy strategies in diseases related to macrophage dysfunction [13,14]. Here, the embryonic origin of the cells may even serve as an advantage [15], and the transplantation of iPSC-derived macrophages potentially may be superior to the transplantation of adult CD34+ HSC-derived macrophages. Consequently, a combination of hematopoietic cell-based gene therapy applications with the unique potential of iPSCs has been explored for quite some time.…”
Section: Resultsmentioning
confidence: 99%